Refleksi Spiritual Leadership Berbasis Qur’ani - Wafi Ali Hajjaj; Siti Aimah (IAI Darussalam, 2020)
Leadership as a process of influencing individuals (personal) or groups to achieve certain goals. Meanwhile, someone who is a role model and must be followed by not deviating from the praises of Allah and the Prophet. This type of qualitative uses a literature study approach, data collecting by searching and collecting data or information related to themes from literature, both in the form of books (books), reports, notes, magazines, newspapers, and others. Meanwhile, the analysis uses historical analysis. The results showed that one of the leadership styles that are recognized as ammunition to achieve better leadership in the future is based on the Qur'anic spiritual leadership. Leadership is a leadership style that puts forward all policies, the performance of an organization rests on values ​​that come from the Qur'an. Starting from the value of honesty, mandate sermon, fatonah, all of these can be applied in any organization to achieve the goals desired and blessed by Allah SWT, S.W.T.